THE CORRELATION AVAILABILITY NURSES AND EQUIPMENT WITH ACUTE MISSED NURSING CARE AT HOSPITALS - Kuswantoro Rusca Putra; Fajar Mulia Dewi; Asih Devi Rahmayanti; Ani Budiati (Indonesian Journal of Health Administration, 2021)
Background: One of the nurse’s roles is to provide nursing care regards of patient safety, consistently and timely.  The availability of nurses and equipment can be considered as a primary constraint contributing to acute missed nursing care.Aims: This study aimed to determine the correlation between the availability of nurses and equipment with incidences of acute missed nursing care in medical and surgical wards at hospitals.Methods: This study used quantitative research with a cross sectional approach. This research was conducted at six private hospitals in Malang from October 2020 to November 2020. The population in this study were selected using consecutive sampling, and the study sample consisted of 206 nurses. The acute MISSCARE Survey was used to collect data. The relationship between the availability of the number of nurses and equipment with acute missed nursing care was analyzed by applying SPSS version 26 with the Spearman test.Results: The relationship between the availability of nurses and acute missed nursing care yielded results of ρ = 0.016 (<0.05) and R = -0.168. Equipment availability and acute missed nursing care had values of ρ = 0.026 (<0.05), and R = -0.155.  This shows correlation between the availability of the number of nurses and equipment with incidences of acute missed nursing care.Conclusion: The availability of the number of nurses and equipment are the reasons for the incidence of acute missed nursing care. Therefore, nursing managers are needed in managing and allocating the necessary number of nurses and equipment.Keywords: equipment, missed nursing care, nurse